Peace, Love, Harmony and Perfection are the Basic Components of Holistic Sustainable Development of the Nations and Civilisation - Suvorov, Nickolay; Suvorova, Iryna (European Journal of Sustainable Development, 2016)
Nickolay Suvorov's book "Man of the Future. – The Perfect Man" was published by International Publishing E.R.A., Moscow-Israel, in 2014 [1]. The book developed a basis for formation of a perfect man – a man of the future, as a holistic complex energy-informational essence. The main result of the book was a scientifically formulated and quantified category of quality and perfection. In this scientific work, the book is presented in the form of three essays: Essay of Peace, Essay of Love, and Essay of Harmony-Perfection. These essays are a collection of 150 short and capacious statements. We believe that the presentation of the book in the form of three essays: Peace, Love, Harmony-Perfection will promote the understanding of the essence and image of Man of the Future – the Perfect Man. The Perfect Man can and must become a reality because the scientific criterion of perfection derived is harmony. Harmony is a footing that will help transform Homo sapiens and form the Perfect Man Keywords: Peace, love, harmony, perfection, perfect man.